STRATEGI KOPING WANITA DEWASA AWAL DITINJAU DARI SPIRITUALITAS DAN RESILIENSI: Strategi Koping - Ummul Aiman Sani (AN-NAFS, 2019)
This study aimed to identify factors influencing coping strategies in early adult women in Penang. A total of 385 early adult women between the ages of 21 and 40 who lived and worked in Penang were respondents to this study. This study was a quantitative study using the Connor - Davidson Resilience Scale (CD-RISC), Daily Spiritual Experience Scale (DSES) and Coping Strategies Inventory Short-Form (CSI-SF) test tool. Pearson correlation and regression analyzes were performed to look at the relationship and influence between spirituality variables, resilience and coping strategies. The results also found that spirituality had a significant positive relationship with coping strategies Focused Engagement (PFE) (r = 0.394, p <0.01) and Emotion Focused Engagement (r = 0.105, p <0.01). However, spirituality was significantly but negatively correlated with Problem Focused Disengagement (PFD (r = -0.230, p <0.01) and Emotion Focused Disengagement (EFD) (r = -0.117, p <0.05). And while there was a significant and positive relationship between resilience and PFE coping strategy (r = 0.557, p <0.01) and EFE coping strategy (r = 0.194, p <0.01), there was a significant and negative relationship between resilience and PFD coping strategy (r = -0.297, p <0.01) and EFD coping strategies (r = -0.246, p <0.01). The results of the regression analysis found that spirituality and resilience gave contribution of 10.5% to early adult females coping strategies in Penang. Key words: Coping strategy, spirituality, resilience Abstrak Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor yang mempengaruhi strategi coping pada wanita dewasa awal di Penang. Sebanyak 385 wanita dewasa awal berusia antara 21 dan 40 tahun yang tinggal dan bekerja di Penang menjadi responden pada penelitian ini. Penelitian ini merupakan penelitian kuantitatif dengan menggunakan skala Connor - Davidson Resilience Scale (CD-RISC), Daily Spiritual Experience Scale (DSES) dan Coping Strategies Inventory Short-Form (CSI-SF) test tool. Analisis korelasi Pearson dan regresi dilakukan untuk melihat hubungan dan pengaruh antara variabel spiritualitas, resiliensi dan strategi coping. Hasil penelitian juga menemukan bahwa spiritualitas memiliki hubungan positif yang signifikan dengan strategi coping Problem Focused Engagement (PFE) (r = 0,394, p < 0,01) dan Emotion Focused Engagement (r = 0,105, p < 0,01). Namun, spiritualitas memiliki hubungan yang signifikan tetapi negatif dengan strategi coping Problem Focused Disengagement (PFD) (r = -0,230, p < 0,01) dan Emotion Focused Disengagement (EFD) (r = -0,117, p < 0,05). Dan juga terdapat hubungan yang signifikan dan positif antara resiliensi dengan strategi coping PFE (r = 0,557, p < 0,01) dan strategi coping EFE (r = 0,194, p < 0,01), terdapat hubungan yang signifikan dan negatif di antara resiliensi dengan strategi coping PFD (r = -0,297, p < 0,01) dan strategi coping EFD (r = -0,246, p < 0,01). Hasil analisis regresi menemukan bahwa spiritualitas dan resiliensi memberikan sumbangan efektif terhadap strategi coping wanita dewasa awal di Penang yaitu sebanyak 10,5%. Key words: Strategi coping, spiritualitas, resiliensi